Employee Recruitment Process During the Covid-19 Pandemic in The IT Sector - Martyna ORKISZ; Ewa BECK-KRALA (Communications of International Proceedings, 2022)
As a result of the COVID-19 pandemic, organizations had to face numerous difficulties and apply many changes to adapt to the new reality. The recruitment process has also changed at the time of the pandemic, as it had to been adapted to the prevailing conditions. The literature review revealed an existing gap in the literature concerning the modification in the recruitment process in the IT companies during the COVID-19. Thus, the aim of the study is to analyze the changes that have occurred in the recruitment process in IT companies during the COVID-19 in Poland. This research was conducted both among recruiters and among employees who took part in such process during the pandemic in large IT companies in Poland. Main focus was placed on examination of the issues such as: the form of recruitment interviews; the number of stages during the recruiting process; the role of AI; and personal feelings of the recruited people in the analyzed period. The authors implemented the triangulation of research sources which allowed for the objectification of the obtained data and the exploration of the issue from several perspectives. The results may be used to draw practical implications for employers representing the IT sector.
Keywords: pandemic; COVID-19; recruitment process; IT sector; Information Technology